Experience in colorectal surgery at a quaternary care hospital in Bogotá, Colombia - J.A. Romo; P.A. Aguilera; A. López; M. Pedraza; C. Figueroa (Revista de Gastroenterología de México (English Edition), 2023)
Introduction and aims: Colorectal cancer is among the three most common cancers worldwide. Knowledge and identification of suboptimal outcome-associated factors enable comprehensive patient management. The aim of the present study was to present the results of the surgical management of colorectal cancer at a quaternary care university hospital. Materials and methods: An observational, analytic, cross-sectional study was conducted. Information was collected on a retrospective cohort of patients diagnosed with colorectal cancer from 2013 to 2017 at the Hospital Universitario Mayor Méderi, Bogotá, Colombia. Results: Data on 452 patients, within the study period, were collected. A total of 48.5% of the patients were men, the overall complication rate was 24%, the surgical site infection (SSI) rate was 15.38%, anastomotic dehiscence occurred in 4.18% of the patients, bleeding required reoperation in 1.32%, and the intrahospital mortality rate was 7.47%. Conclusion: Colorectal cancer management at a university hospital was as beneficial as that provided by other types of hospitals, showing a direct association with complete R0 dissections; low complication rates, according to international reports; and reduced overall morbidity. Resumen: Introducción y objetivos: El cáncer colorrectal se encuentra dentro de los 3 primeros cánceres a nivel mundial, el conocimiento e identificación de los factores asociados a los desenlaces no óptimos permiten realizar un manejo integral del paciente. El objetivo de este estudio es presentar los resultados del manejo quirúrgico de enfermedad oncológica colo-rectal en un hospital universitario de cuarto nivel. Materiales y métodos: Se realizó un estudio observacional, analítico de corte transversal, se recolectó la información de una cohorte retrospectiva de pacientes con diagnóstico de cáncer colorrectal entre el año 2013 al año 2017 en el Hospital Universitario Mayor Méderi, Bogotá, Colombia. Resultados: Se recolectaron 452 pacientes durante el periodo de estudio, de estos el 48.5% fueron varones. El porcentaje global de complicaciones fue del 24%, infección del sitio operatorio (ISO) en el 15.38%, dehiscencia de la anastomosis en el 4.18%, sangrado que origina reintervención en el 1.32% y mortalidad intrahospitalaria en el 7.47%. Conclusión: El manejo del cáncer colorrectal en un hospital universitario mostró beneficios y resultados similares y comparables con otros tipos de hospitales con manejo frecuente de esta enfermedad, mostrando una asociación directa en disecciones completas R0, con bajas tasas de complicaciones según lo reportado a nivel mundial y disminución de morbilidad global.